Answer:
....bbbbbb.... its correct
Answer:
The solved given fractional expression is ![\frac{17}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B17%7D%7B3%7D)
Therefore the given fractional expression becomes
![\frac{6}{2}+\frac{8}{3}=\frac{17}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7B2%7D%2B%5Cfrac%7B8%7D%7B3%7D%3D%5Cfrac%7B17%7D%7B3%7D)
Step-by-step explanation:
Given fractional expression is ![\frac{6}{2}+\frac{8}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7B2%7D%2B%5Cfrac%7B8%7D%7B3%7D)
To solve the given fractional expression as below :
![\frac{6}{2}+\frac{8}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7B2%7D%2B%5Cfrac%7B8%7D%7B3%7D)
( here taking the term 3 as LCM )
( by adding the sums here )
![=\frac{17}{3}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B17%7D%7B3%7D)
![\frac{6}{2}+\frac{8}{3}=\frac{17}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7B2%7D%2B%5Cfrac%7B8%7D%7B3%7D%3D%5Cfrac%7B17%7D%7B3%7D)
Therefore the solved given fractional expression is ![\frac{17}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B17%7D%7B3%7D)
Therefore the given fractional expression becomes
![\frac{6}{2}+\frac{8}{3}=\frac{17}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7B2%7D%2B%5Cfrac%7B8%7D%7B3%7D%3D%5Cfrac%7B17%7D%7B3%7D)
The solved given fractional expression is ![\frac{6}{2}+\frac{8}{3}=\frac{17}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7B2%7D%2B%5Cfrac%7B8%7D%7B3%7D%3D%5Cfrac%7B17%7D%7B3%7D)